Digital steganography model and its formal description - Haitao SONG; Guangming TANG; Yifeng SUN; Yang WANG (网络与信息安全学报)
In order to make the research of digital steganography model develop synchronously with steganography research,three digital steganography models from general to specific are proposed,and each model was formalized.Through study on digital model,the essential principles of steganography algorithm were summarized to guide the further development of steganography.Firstly,aiming at the problem that the existing model cannot describe the emerging steganography algorithms,a general digital steganography model was proposed to describe nearly all steganography algorithms.Secondly,in view of the important position of the cover modification steganography algorithm in the research of steganography,a cover-modification digital steganography model was proposed.Then,for the current mainstream image adaptive steganography algorithm,a digital image adaptive steganography model with minimal distortion was proposed.Four typical steganography algorithm were selected as examples which were described by the proposed steganography model to validate the effectiveness of the proposed model.